Increasing the Strength of Sintered Body Hydroxyapatite (HA) with the Addition of Alumina as Reinforcing Material - Femil aulia ihsan; Ade Indra; Subardi (ReTII, 2022)
Sintered body hydroxyapatite (HA)-alumina (Al2O3) in the form of pellets was made by varying the sample ratio. HA-alumina particles were prepared in various ratios from 97:3%, 94:6%, 92:8%, 88:12%, 85:15%, 82:18% (%wt). Commercial HA and commercial alumina were used as test materials with the addition of polyvinyl alcohol (PVA). Commercial HA and commercial alumina were wet mixed for 2 hours for each sample variation. Each sample used will be mixed with PVA as much as 5% by weight and 5gr of alcohol. The mixing process uses a rotary mixer with the addition of 10 alumina ball mills. After the mixing process, the samples were dried for 48 hours to remove the alcohol contained therein. Furthermore, the printing process to produce a green body is carried out by the uniaxial pressing method at a pressure of 100 MPa and held for 3 minutes. The mold size used has a diameter of 8mm and a thickness of 3.3mm. The sintering process is carried out to obtain a sintered body, and sintering is carried out at a temperature of 1200ËšC with a heating rate of 3ËšC/minute and a holding time of 2 hours. Then the temperature was lowered to 800ËšC with a cooling rate of 3ËšC/minute. Then the temperature was lowered to 300ËšC with a cooling rate of 5ËšC/minute. In the linear shrinkage test, there was an insignificant decrease in weight loss and diameter shrinkage. The weight loss decreased from 45.67% - 34.65%. In diameter shrinkage, there was a decrease from 11.15% - 8.86%. In the density and relative density tests, there was an insignificant increase in each ratio. In relative density there is an increase from 41.71% - 46.00%. In density, there is an increase from 1.32% - 1.52%. In the compressive strength test, the highest value was found at the HA-alumina ratio of 97:3 wt% with a value of 28.6 MPa, and the lowest value was found in the HA-alumina ratio of 88:12 wt% with a value of 13.0 MPa. Keywords: hydroxyapatite, alumina, pressureless sintering, compressive strength